2011
DOI: 10.1080/15599612.2011.559685
|View full text |Cite
|
Sign up to set email alerts
|

An Improvement of Scanning Ellipsometer by Rotating a Polarizer and an Analyzer at a Speed Ratio of 1:3

Abstract: We propose theoretically an improved spectroscopic ellipsometer to study the optical properties of solids. In this system, the polarizer and the analyzer are rotating synchronously in the same direction at a speed ratio 1:3. The light intensity received by the detector contains six Fourier coefficients, one dc and five ac. One can independently extract the ellipsometric parameters as well as the optical constants of a sample using any of six different sets of the Fourier coefficients. A comparison among these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…It was shown that in Ref. [16] that the first two sets correspond to the minimum error compared to other sets. The parameters ψ and Δ in terms of the first set are given by a a a a a a…”
Section: Theorymentioning
confidence: 96%
See 4 more Smart Citations
“…It was shown that in Ref. [16] that the first two sets correspond to the minimum error compared to other sets. The parameters ψ and Δ in terms of the first set are given by a a a a a a…”
Section: Theorymentioning
confidence: 96%
“…It is worth to mention that these valu s m of ψ and Δ were calculated using the coefficients a 1 , a 2 , and a 3 without depending on the dc offset of the signal for the clean and the noisy signals. If the dc term is considered in the calculations, the percent error in ψ and Δ would be much higher [14][15][16]. This ellipsometer in which the polarizer and the analyzer rotate in the same direction with a speed ratio 1:3 has the advantage that the results do not depend entirely on this term.…”
Section: Numerical Calculationsmentioning
confidence: 99%
See 3 more Smart Citations